1970
DOI: 10.1139/v70-114
|View full text |Cite
|
Sign up to set email alerts
|

Detection and chemistry of the triplet state of thymine

Abstract: The transient produced on flash excitation of degassed solutions of thymine in acetonitrile has been characterized as the triplet excited state of thymine. This triplet state has a lifetime of 14 + 1 ps and the associated dimerization rate was found to be 5.3 + 0.3 x 10' M-' s-' . The triplet state of thymine could be quenched by 2,4-hexadien-1-01 with a rate constant of 8.1 + 0.6 x lo9 M-' s-'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1976
1976
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…This process can also be facilitated by the additional stabilization of thymine triplet 3 T due to π-stacking, and the related multichromophoric coupling in the DNA helical structure. Thymine photochemistry has been explored as early as 1960s (11), but the presence of 3 T (12) has triggered renewed attention, notably for delineating the mechanism of triplet-triplet energy transfer with external photosensitizers (13), or with modified nucleobases and oxidative lesions recognized as Trojan Horses (9,14). It has also been shown that the population of 3 T opens rather efficient photochemical channels for dimerization (15,16), even if there is no experimental evidences for the formation of 64-PP mediated by 3 T. The energy of 3 T in a DNA strand has been inferred experimentally by Bosca et al by assessing the energy transfer efficiency of different photosensitizers, such as norfloxacin and its N4'-acetyl derivative, whose energies are precisely known (17).…”
Section: Introductionmentioning
confidence: 99%
“…This process can also be facilitated by the additional stabilization of thymine triplet 3 T due to π-stacking, and the related multichromophoric coupling in the DNA helical structure. Thymine photochemistry has been explored as early as 1960s (11), but the presence of 3 T (12) has triggered renewed attention, notably for delineating the mechanism of triplet-triplet energy transfer with external photosensitizers (13), or with modified nucleobases and oxidative lesions recognized as Trojan Horses (9,14). It has also been shown that the population of 3 T opens rather efficient photochemical channels for dimerization (15,16), even if there is no experimental evidences for the formation of 64-PP mediated by 3 T. The energy of 3 T in a DNA strand has been inferred experimentally by Bosca et al by assessing the energy transfer efficiency of different photosensitizers, such as norfloxacin and its N4'-acetyl derivative, whose energies are precisely known (17).…”
Section: Introductionmentioning
confidence: 99%
“…In solution, for the majority of molecules in the pyrimidine family, excitation is accompanied by an accumulation of lone electrons at C5 and C6 and a marked reduction in bond order. , Dimerization occurs through the generation of a singlet state, followed by intersystem crossing and decay to a triplet state, from which the dimer is formed. The lifetime of the excited triplet state is much longer than the singlet state and energy is normally dissipated by chemical routes, since there is ample opportunity for molecules to diffuse and collide in solution.…”
Section: Introductionmentioning
confidence: 99%
“…This process can also be facilitated by the additional stabilization of thymine triplet ( 3 T) due to ⇡ stacking, and the related multichromophoric coupling in the DNA helical structure. Thymine photochemistry has been explored as early as 1960s 11 , but the presence of 3 T 12 has triggered renewed attention, notably for delineating the mechanism of triplet-triplet energy transfer with ex-ternal photosensitizers 13 , or with modified nucleobases and oxidative lesions recognized as Trojan Horses 9,14 . It has also been shown that the population of 3 T opens rather e cient photochemical channels for dimerization, and especially for the production of 64-PP.…”
Section: Introductionmentioning
confidence: 99%